Disruptions of working memory and inhibition mediate the association between exposure to institutionalization and symptoms of attention deficit hyperactivity disorder. Issue 3 (16th October 2015) - Tibu, F.; Sheridan, M. A.; McLaughlin, K. A.; Nelson, C. A.; Fox, N. A.; Zeanah, C. H.
Abstract : Background: Young children raised in institutions are exposed to extreme psychosocial deprivation that is associated with elevated risk for psychopathology and other adverse developmental outcomes. The prevalence of attention deficit hyperactivity disorder (ADHD) is particularly high in previously institutionalized children, yet the mechanisms underlying this association are poorly understood. We investigated whether deficits in executive functioning (EF) explain the link between institutionalization and ADHD. Method: A sample of 136 children (aged 6–30 months) was recruited from institutions in Bucharest, Romania, and 72 never institutionalized community children matched for age and gender were recruited through general practitioners' offices. At 8 years of age, children's performance on a number of EF components (working memory, response inhibition and planning) was evaluated. Teachers completed the Health and Behavior Questionnaire, which assesses two core features of ADHD, inattention and impulsivity. Results: Children with history of institutionalization had higher inattention and impulsivity than community controls, and exhibited worse performance on working memory, response inhibition and planning tasks. Lower performances on working memory and response inhibition, but not planning, partially mediated the association between early institutionalization and inattention and impulsivity symptom scales at age 8 years. Conclusions: Institutionalization was associated with decreased EF performance and increased ADHD symptoms. Deficits in working memory and response inhibition were specific mechanisms leading to ADHD in previously institutionalized children. These findings suggest that interventions that foster the development of EF might reduce risk for psychiatric problems in children exposed to early deprivation.